Experiments in Wheat Control: The Agricultural Adjustment Act, 1933 - Davis, Joseph S. (Quarterly Journal of Economics, 1935)
Experiments in Wheat Control: The Agricultural Adjustment Act, 1933 Get access Joseph S. Davis Joseph S. Davis Food Research Institute, Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 2, February 1935, Pages 358–363, https://doi.org/10.2307/1884071 Published: 01 February 1935